Controllable Synthesis of Multicompartmental Particles Using 3D Microfluidics. (19th December 2019) - Wu, Zengnan; Zheng, Yajing; Lin, Ling; Mao, Sifeng; Li, Zenghe; Lin, Jin‐Ming
Abstract: A microfluidic assembly method based on a microfluidic chip and capillary device was developed to create multicompartmental particles. The microfluidic chip design endows the particles with regulable internal structure. By adjusting the microstructure of the chip, the diameter of the capillary, the gap length between the two microfluidic components, and the flow rates, the size of the particles and the number or the ratio of different regions within the particle could be widely varied. As a proof of concept, we have produced some complicated particles that even contain 20 compartments. Furthermore, the potential applications of the anisotropic particles are explored by encapsulating magnetic beads, fluorescent nanoparticles, and the cells into different compartments of the microparticles. We believe that this method will open new avenues for the design and application of multicompartmental particles. Abstract : Kapselmaschine : Ein Mikrofluidikgerät aus einem mikrofluidischen Chip und Kapillarrohr wurde für die Herstellung multikompartimentierter Partikel entwickelt. Durch Einstellen verschiedener Geräteparameter konnten die Größe und die Kompartimentzahl der Partikel variiert werden. Diese wurden zur Verkapselung von magnetischen Partikeln, fluoreszierenden Nanopartikeln und Zellen genutzt.